توحيد قواعد قانون التجارة الدولية في إطار المنظمات الدولية الحكومية - حواس, عشوي; محند, زايد (جامعة مولود معمري تيزي وزو, 2023)
يتطلب توحيد قواعد قانون التجارة الدولية جهودا ووسائل معتبرة، الأمر الذي جعل المنظمات الدولية الحكومية هي التي تتكفّل بهذه المهمّة. وتنقسم هذه المنظمات الدولية الحكومية إلى منظمات دولية عالمية، ومنظمات دولية إقليمية. اتبعت هذه الأخيرة أساليب متعددة للتوحيد، من اتفاقيات دولية وقوانين نموذجية وقوانين موحّدة. وأمام تعدّد أساليب التوحيد هذه، يجب اختيار الأسلوب الأكثر ملاءمة لضمان فعّالية عملية التوحيد. لكن، رغم الجهود المبذولة من قبل هذه المنظمات، فإنها لم تصل إلى التوحيد الكلّي لهذه القواعد، وذلك بسبب اختلاف الأنظمة السياسية والاجتماعية للدول، فلم يشمل التوحيد إلاّ بعض مجالات القانون. كما بقيت القواعد الموحدة صعبة التطبيق لاختلاف تفسيرها من جهة، ولقلّة خبرة القضاة والمحكّمين في هذا المجال من جهة أخرى. L'unification des règles du droit du commerce international nécessite des efforts et des moyens considérables, ce pourquoi cette tâche a été confiée aux organisations gouvernementales internationales. Ces organisations intergouvernementales sont divisées en organisations internationales mondiales et organisations internationales régionales.Ces dernières ont suivi de multiples méthodes d’unification, notamment des accords internationaux, des lois types et des lois unifiées.Face à ces multiples méthodes d’unification, il faut choisir la méthode laplus appropriée pour garantir l’efficacité du processus d’unification. Cependant, malgré les efforts déployés par ces organisations, elles ne sont pas parvenues à une unification complète de ces règles, en raison des différences entre les systèmes politiques et sociaux des pays. L'unification n'a porté que sur certains domaines du droit. Les règles unifiées restent également difficiles à appliquer en raison de leurs interprétations différentes d'une part, et du manque d'expérience des juges et des arbitres dans ce domaine, d'autre part.

التجارة الالكترونية بين الواقع والتحديات في الجزائر في ظل تطور استخدام تكنولوجيا المعلومات والاتصال - بغداد, عبد القادر; بن زيدان, الحاج (Ibn Khaldun University of Tiaret, 2023)
تهدف دراستنا الى التعرف على ظاهرة التجارة الالكترونية التي اصبحت حقيقة واقعية انتشرت بصورة كبيرة في وقت قصير، مع إيضاح مكانة التجارة الالكترونية في الجزائر مع تحديد و معرفة أهم التحديات والعوائق التي تواجه الجزائر في استخدام هذه التجارة. رغم ما ذكر آنفا ، نجد ان الجزائر قطعت شوطا كبيرا في تبنيها لهذه التجارة الحديثة ، فقد اتخذت مؤخرا إجراءات عدة في جميع الميادين بغية تدعيم استخدام التقنيات الحديثة ومسايرة التحولات التكنولوجية من اجل تبني التجارة الالكترونية وتذليل العقبات ووضع استراتيجيات وسياسات وطنية للتقدم العلمي والتأهيل المؤسساتي والقانوني من اجل النهوض بالاقتصاد الوطني . توصلت الدراسة الى ان ضعف تمويل التجارة الالكترونية يفرض على الجزائر تشجيع مساهمة القطاع الخاص والمشترك في تمويل هذه التجارة ، تكييف القواعد القانونية الحالية وهذا ما يمثل الهدف الأساسي للقانون 18-05 المتعلق بالتجارة الالكترونية ، الذي سمح بضمان أمن التجارة الالكترونية ، مما يسمح بتنشيط وتحفيز المؤسسات لاقتحام هذا النشاط والارتقاء بمستوى التعاملات التجارية الالكترونية Our study aims to identify the phenomenon of E-commerce , which has become a realistic reality and has spread widely in a short time, with an explanation of the status of E-commerce in Algeria, while identifying and knowing the most important challenges and obstacles facing Algeria in the use of this trade. Despite what was mentioned above, we find that Algeria has come a long way in adopting this modern trade. It has recently taken several measures in all fields in order to support the use of modern technologies and keep pace with technological transformations in order to adopt E-commerce and overcome obstacles and develop national strategies and policies for scientific progress and institutional and legal rehabilitation from for the advancement of the national economy. The study concluded that the weakness of financing E-commerce requires Algeria to encourage the contribution of the private sector and the participant in financing this trade, adapting the current legal rules, and this represents the main objective of Law 18-05 related to E-commerce , which allowed ensuring the security of E-commerce, which allows stimulating and stimulating institutions To break into this activity and raise the level of electronic commercial transactions.
Keywords: Commerce électronique; Enjeux du commerce électronique en Algérie; Paiement électronique; Technologies de l'information et de la communication; التجارة الإلكترونية; الدفع الالكتروني; تحديات التجارة الالكترونية في الجزائر; تكنولوجيا المعلومات والاتصالات

أساس المسؤولية الجزائية لجرائم الشركات التجارية - دحو, خديجة; دهلي, حبيبة (Ibn Khaldun University of Tiaret, 2023)
مسؤولية الشركات التجارية في الجانب الجنائي هي مفهوم قانوني يحدد امكانية مساءلة الشركات او المؤسسات التجارية جنائيا عن الجرائم التي ترتكب في اطار أنشطتها. تاريخيا كان يتم ملاحقة ومساءلة الأفراد جنائيا فقط عن افعالهم الاجرامية ومع طفرة قانون الأعمال وتزايد الوعي بضرورة مساءلة الشركات اصبحت مسؤولية الشركات التجارية جزائيا واقعا في العديد من البلدان. Corporate criminal liability is a legal concept that determines the possibility of holding corporations or commercial entities criminally accountable for crimes committed within the scope of their activities. Historically, only individuals were pursued and held criminally responsible for their criminal actions. However, with the evolution of business law and increased awareness of the need to hold corporations accountable, corporate criminal liability has become a reality in many countries Corporate criminal liability is based on the principle that a corporation can be considered an independent entity separate from its directors, employees, and shareholders. Therefore, if a criminal offense is committed within the company's operations, it can be prosecuted and tried independently of the individuals associated with it. The specific criminal offenses for which corporations can be held accountable vary according to national legislation, but they typically include acts such as fraud, bribery, money laundering, tax evasion, environmental violations, human rights abuses, forgery, unfair competition, and others. When a corporation is criminally prosecuted, it can face severe penalties, including hefty fines, asset seizure, dissolution of the
Keywords: Droit des sociétés commerciales; Personnes morales; Responsabilité pénale; الشخصية الاعتبارية; الشركات التجارية; المسؤولية الجنائية

تبني البنوك التجارية التقليدية للمعاملات المصرفية الإسلامية - زرفاط, خليدة; سوالمي, رحاب نور الهدى (جامعة ابن خلدون-تيارت, 2023)
تمثل البنوك التجارية الجزائرية المعبر الرئيسي للوساطة المالية والمصرفية في الاقتصاد الوطني، إذ تساهم بشكل كبير في أغلب المعاملات الاقتصادية داخل وخارج الوطن، وبالتالي فهي تساهم بعدة أدوار مهمة في التنمية الاقتصادية واستدامتها عبر الأجيال، قام ت الحكومة بإنشاء فروع ونواف ذ إسلامية للمعاملات المالية الإسلامية على مستوى هذه البنوك وطرح منتجات مصرفية إسلامية قرر ساعد على جذب المتعاملين بالسوق الموازية لضخ أموالهم بالبنوك الوطنية واستخدامها بصيغ تطبق احكام الشريعة الإسلامية، تعمل الصيرفة الإسلامية على نبذ الربا وتعزيز التكافل الاجتماعي والعدالة. إن استخدام مثل هذه الخدمات يهدف إلى تحقيق المشاركة في الأرباح والخسائر بين البنوك والزبائن. وفي دراستنا تبين لنا مدى تبني البنوك التقليدية الجزائرية للمعاملات المالية الإسلامية من خلال فتح نوافذ إسلامية تعمل وفق الشريعة الإسلامية لتحقيق رضا وإستقطاب الزبائن Algerian commercial banks represent the main catalyst for financial and banking intermediation in the national economy. They to contribute significantly the majority of economic transactions within and outside the country. Consequently, they play several crucial roles in economic development and its sustainability across generations. The government has established branches and windows for Islamic financial transactions in these banks and introduced Islamic banking products. This decision has helped attract participants in the parallel market to channel their funds into national banks and utilize them in accordance with Islamic law principles. Islamic banking aims to eliminate usury (riba) and promote social solidarity and justice. The use of such services aims to achieve profit and loss sharing between banks and customers. Our study has revealed the extent to which Algerian traditional banks have embraced Islamic financial transactions by opening Islamic windows that operate in accordance with Islamic law, aiming to achieve customer satisfaction and attract clients
Keywords: Commercial banks; Customer satisfaction; Financial transactions; Islamic Banking; Islamic windows

تحديات فرض الضرائب على معاملات التجارة الإلكترونية في الجزائر - مبخوت, رفيق; غول, حسين (Ibn Khaldun University of Tiaret, 2023)
لقد تطرّقنا في موضوع دراستنا على تحدّيات فرض الضّرائب على معاملات التّجارة الإلكترونية باعتبار موضوع التّجارة الإلكترونية من المواضيع الهامّة التي تلقى اهتماما كبيرا من قبل الكثير من الباحثين لما لها من انعكاسات على اقتصاديات دول العالم المتقدّمة والنّامية، حيث تعدّ إحدى النّظم الحديثة في إتمام وتنفيذ المعاملات التّجارية عبر شبكات الأنترنت. ولقد أسفرت دراستنا الميدانية في المركز الجواري للضّرائب دائرة السّوقر التي واجهت عدّة صعوبات لإخضاع المعاملات الإلكترونية بسب غياب قوانين والتّشريعات المتعلّقة بتنظيم الضّريبة الإلكترونية وغياب رقمنة القطاع وصعوبات تقنية تطبيق هذا النّوع من الضّرائب. هذا ما أوجب على الجزائر بذل مجهوداتها من أجل دعم وإرساء البنية التحتية للاتّصالات ومسايرة التّقدّم التّكنولوجي في العالم وتسليط الضّوء على القوانين والتّشريعات الجبائية الخاصّة بهذه التّجارة وسَنّها والعمل بها على أرض الواقع. In the subject of our study, we have addressed the challenges of imposing taxes on electronic commerce transactions, considering the issue of electronic commerce as one of the important topics that receive great attention by many researchers because of its implications for the economies of the developed and developing countries of the world, as it is one of the modern systems in the completion and implementation of commercial transactions. Via internet networks. Our field study resulted in the neighborhood tax center, in Sougueur Department, which faced several difficulties in subjecting electronic transactions due to the absence of laws and legislation related to the organization of electronic taxation, the absence of digitization of the sector, and the technical difficulties of applying this type of taxation. This is what required Algeria to exert its efforts to support and establish the telecommunications infrastructure, keep pace with the technological progress in the world, shed light on the laws and fiscal legislation related to this trade, enact them and implement them on the ground.
Keywords: Algeria; Algérie; Commerce électronique; Fiscalité; Internet; Taxe électronique; الأنترنت; التجارة الإلكترونية; الضريبة الإلكترونية; النظام الضريبي

حماية الغير في الشركات التجارية - محوز, العالية; سليمان, عائشة (Ibn Khaldun University of Tiaret, 2023)
تحتل حماية الغير المتعامل مع الشركات التجارية مكانة مهمة في القانون التجاري حيث كرس لها المشرع العديد من الأحكام والمبادئ القانونية التي تساهم في إستقرار المعاملات التجارية للشركات التجارية من جهة، والتي تدعم الثقة في معاملات الشركة مع محيطها الخارجي من جهة أخرى، وذلك نظرا للدور الذي يؤديه الغير في تطوير و إزدهار الشركة وتشجيع المتعاملين للإستثمار في هذا القطاع الاقتصادي المهم. قام المشرع بخطوات مهمة جعل من خلالها الغير يتدخل في حياة الشركة ونشاطها وذلك تخفيفا لآثار إعتبار هذا الغير عضوا خارجيا لا علم له بما يجري داخل الشركة التجارية، لكن تبني المشرع لأنظمة قانونية من أجل الغير لا يعني بلوغ النصوص القانونية هدفها الذي قررت من أجله . The protection of third parties dealing with commercial companies occupies an important place in the commercial law, as the legislator devoted many legal provisions and principles to it that contribute to the stability of commercial transactions of commercial companies on the one hand, and that support confidence in the company’s transactions with its external environment on the other hand, due to the role it plays Others contribute to the development and prosperity of the company and encourage customers to invest in this important economic sector. The legislator took important steps through which he made third parties interfere in the life and activity of the company in order to mitigate the effects of considering this third party as an external member who has no knowledge of what is going on inside the commercial company, but the legislator’s adoption of legal systems for the sake of third parties does not mean that the legal texts have reached their goal for which they were decided

تأسيس شركات المساهمة في التشريع الجزائري - يعقوبي, محمد (Ibn Khaldun University of Tiaret, 2023)
شركة المساهمة هي شركة أموال، لا يقل عدد شركائها عن سبعة شركاء يسمون بالمساهمين تتمثل حصصهم في الشركة بأسهم متساوية القيمة سهلة التداول لا يسأل هؤلاء عن ديون الشركة الا في حدود قيمة الأسهم التي اكتتبوا فيها، وكأي شركة وجب توفر الأركان الموضوعية العامة والخاصة والشكلية وإذا اختلف أحد هذه الأركان يعرضها للبطلان إما نسبي أو مطلق. وضع المشرع الجزائري طريقتين لتأسيس شركة المساهمة إما باللجوء العلني للادخار أو بدون اللجوء العلني للادخار أو بما يعرف بالتأسيس الفوري وتتميز المرحلتين بإجراءات معقدة، يقوم المؤسسون في كلتي المرحلتين بإعداد القانون الأساسي عن طريق جمعية عامة تأسيسية والمصادقة على الشروط المتفق عليها ووضع الشركة للجمهور قصد الاكتتاب فيها إذا ما لجأ المؤسسون لطريقة اللجوء العلني للادخار . أخيرا تسجيل الشركة في السجل التجاري كخطوة أخيرة من مراحل تأسيس الشركة. وأي مخالفة من شأنها تعطيل السير الحسن لتأسيس الشركة يعرضها للبطلان وتعدا المشرع البطلان إلا قيام مسؤولية مدنية وجزائية بتسليط عقوبات رادعة في حق المتخاذلين والمتعمدين في إفشال مشروع الشركة. A joint stock company is a company of funds, the number of its partners is not less than seven partners called shareholders whose shares in the company are represented by shares of equal value easy to trade, these are not responsible for the company's debts except within the limits of the value of the shares in which they subscribed, and like any company, we must provide the general, private and formal pillars, and if one of these pillars differs, it exposes it to invalidity, either relative or absolute. The Algerian legislator has developed two ways to establish a joint stock company, either by public resort to savings or without public resort to saving, or what is known as immediate incorporation, and the two stages are characterized by complex procedures, the founders in both stages prepare the basic law through a constituent general assembly, ratify the agreed terms and place the company for the public in order to subscribe to it if the founders resort to the method of public resort to savings, so that the company is finally registered in the commercial register as a final step of the company's establishment Any violation that may disrupt the proper functioning of the establishment of the com-pany exposes the company to invalidity and the legislator transgresses the nullity, except for civil and criminal liability to impose deterrent penalties against the negligent and deliberate in thwarting the company's project
Keywords: Création d'entreprise; Socitété par action; الإدخار; الإكتتاب